Plated steel material

By adjusting the Al phase ratio and phase composition in the Zn-Al-Mg-based plating layer, the problem of insufficient corrosion resistance of existing plated steel plates in water-wet and running environments is solved, and high water-wet corrosion resistance, running water corrosion resistance and replacement corrosion resistance are achieved.

CN119744315APending Publication Date: 2025-04-01NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380061348.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing Zn-Al-Mg-based plated steel plates are insufficient in water-wet and running environments, and the corrosion resistance of replacement is difficult to meet the requirements.

Method used

By adjusting the Al phase ratio in the plating layer and controlling the area ratio of the MgZn2 phase, Al-Zn phase and Zn-Al phase, the chemical composition and structural structure of the plating layer are within a specific range, and improving water-wet corrosion resistance, running water corrosion resistance and replacement corrosion resistance.

Benefits of technology

It realizes the coated steel with excellent corrosion resistance and replacement corrosion resistance in water-wet and running environments, extending the service life of the steel structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005281055230000281
    Figure BDA0005281055230000281
  • Figure BDA0005281055230000291
    Figure BDA0005281055230000291
  • Figure BDA0005281055230000301
    Figure BDA0005281055230000301
Patent Text Reader

Abstract

This plated steel material has a steel material and a plating layer disposed on the surface of the steel material, and the average chemical composition of the plating layer contains a prescribed composition. The structure observed with a scanning electron microscope comprises, in area fraction, 10%-50% of a MgZn2 phase, 15%-75% of a total of an Al phase, an Al-Zn phase, and a Zn-Al phase, 0%-65% of a (Al / MgZn2 / Zn ternary eutectic structure, and 0%-5.0% of a remainder, and the area ratio of the total of the Al phase and the Zn-Al phase to the Al-Zn phase (([Al] + [Zn-Al]) / [Al-Zn]) is 0.8 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to coated steel.

[0002] This application claims priority based on Japanese Patent Application No. 2022-136497 filed in Japan on August 30, 2022, and the contents are incorporated herein by reference. Background Art

[0003] It is well known that the corrosion resistance of steel is improved by plating Zn on the surface of steel. Among them, Zn-Al-Mg plated steel sheets with improved corrosion resistance by adding Al and Mg to Zn are often used in the fields of automobiles, home appliances, building materials, and civil engineering. In the environments of these uses, there are wet environments with constant accumulation of rainwater and flowing water environments, but even Zn-Al-Mg plated steel sheets have the problem of insufficient corrosion resistance in these environments.

[0004] For example, Patent Document 1 describes a Zn-Al-Mg based plated steel sheet, which comprises a steel sheet, an alloy layer comprising Fe and Si, and a plated layer, wherein the average composition of the plated layer and the alloy layer comprises, by mass%, Al: 45.0-65.0%, Si: 0.50-5.00%, Mg: 1.00-10.00%, and the remainder comprises Zn, Fe, and impurities, and the plated layer comprises, by volume fraction, 0.1-20.0% of a Mg-Si phase, and a portion of the plated layer is 1 μm from the surface of the plated layer in the thickness direction of the plated layer. When the range of m is defined as the surface part of the coating, the average equivalent circle diameter of the Mg-Si phase in the direction of the coating looking down at the surface part is 0.1 to 15.0 μm, and the position of 1 / 2 of the thickness of the coating from the surface of the coating toward the interface between the coating and the alloy layer is defined as the center of the coating thickness, and when the Si content is measured over the entire thickness of the coating, the cumulative value of the Si content from the surface of the coating to the center of the coating thickness is more than 0.55 times the cumulative value of the Si content from the surface of the coating to the interface.

[0005] Patent document 2 describes a hot-dip Al-Zn-Mg-Si steel plate having a plated film on the surface of the steel plate, wherein the plated film includes an interface alloy layer present at the interface with the base steel plate and a main layer present on the alloy layer, containing 25 to 80 mass % of Al, more than 0.6 mass % and less than 15 mass % of Si, and more than 0.1 mass % and less than 25 mass % of Mg, and the area ratio of Mg2Si in the surface of the main layer is more than 10%.

[0006] Patent document 3 describes a method for forming a metal-coated strip, which is a method for forming a steel strip, comprising the following steps: (a) a step of passing the strip through a hot-dip coating bath containing Al, Zn, Si and Mg, and other elements as required, to form a molten Al-Zn-Si-Mg alloy coating on the strip; (b) a step of cooling the coated strip to solidify the molten Al-Zn-Si-Mg alloy on the strip to form a solidified coating having a microstructure containing α-Al phase dendrites, Zn-rich phases in interdendritic regions, and Mg2Si phase particles in interdendritic regions; (c) a step of heat treating the coated strip at a temperature and time to form an Al-Zn phase solid solution from an as-cast microstructure of α-Al phase dendrites and Zn-rich interdendritic phases to promote spheroidization of Mg2Si phase particles dispersed in the coating; and (d) a step of cooling the strip after the heat treatment.

[0007] Patent document 4 describes a high heat-resistant hot-dip Zn-Al alloy steel plate, which has an alloy coating composed of 3.0 to 7.0 mass % Al, 0.05 to 0.5 mass % Si, 0.01 to 0.5 mass % Mg, and the remainder Zn on the surface of the steel plate, and a Fe-Al-Si alloy layer with concentrated Si is formed between the alloy coating and the steel plate substrate.

[0008] Patent document 5 describes a hot-dip Zn-Al-Mg steel material, which has a plating layer formed on the surface of the steel material, the plating layer contains Mg: 1 to 10 mass%, Al: 4 to 22 mass%, and the remainder contains Zn and impurities in terms of average composition, in the plating layer, in a matrix of [ternary eutectic structure of Al / Zn / MgZn2], contains [Al·Zn mixed structure] with an area ratio of 10 to 70% in the cross section of the plating layer, in the [Al·Zn mixed structure], contains a first region with a Zn concentration in the range of 75 mass% or more and less than 85 mass%, and a second region located inside the first region and with a Zn concentration in the range of 67 mass% or more and less than 75 mass%, in which a Zn phase and an Al phase are mixed, and every 1 μm of the second region in the cross section of the plating layer 2 The area length of the interface between the Zn phase and the Al phase is 20 μm or less.

[0009] However, in Patent Documents 1 to 5, corrosion resistance in a wet environment or a flowing water environment (hereinafter referred to as wet corrosion resistance or flowing water corrosion resistance) has not been studied.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: International Publication No. 2019 / 049307

[0013] Patent Document 2: Japanese Patent Application Publication No. 2016-166414

[0014] Patent Document 3: Japanese Patent Application No. 2012-528244

[0015] Patent Document 4: Japanese Patent Application Publication No. 2000-265255

[0016] Patent Document 5: Japanese Patent Application Publication No. 2021-195564 Summary of the invention

[0017] Problems to be solved by the invention

[0018] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a plated steel material having excellent wet corrosion resistance and running water corrosion resistance and also excellent chemical corrosion resistance.

[0019] Means for solving problems

[0020] In order to solve the above-mentioned problems, the following configuration is adopted.

[0021] [1] A plated steel material comprising a steel material and a plating layer disposed on a surface of the steel material,

[0022] The average chemical composition of the above-mentioned coating includes, by mass %, the following:

[0023] Al: 10.0% to 40.0%,

[0024] Mg: more than 4.0% and less than 8.5%,

[0025] Si: 0% to 5.0%,

[0026] Ca: 0% to 3.00%,

[0027] Sn: 0% to 3.00%,

[0028] Bi: 0% to 1.00%,

[0029] In: 0%~1.00%,

[0030] Y: 0% to 0.50%,

[0031] La: 0% to 0.50%,

[0032] Ce: 0% to 0.50%,

[0033] Sr: 0% to 0.50%,

[0034] B: 0%~1.00%,

[0035] P: 0%~0.50%,

[0036] Cr: 0% to 0.25%,

[0037] Ti: 0% to 0.25%,

[0038] V: 0%~0.25%,

[0039] Zr: 0% to 0.25%,

[0040] Ni: 0% to 1.00%,

[0041] Co: 0% to 0.25%,

[0042] Nb: 0% to 0.25%,

[0043] Cu: 0% to 1.00%,

[0044] Mn: 0% to 0.25%,

[0045] Mo: 0% to 0.25%,

[0046] W: 0%~0.25%,

[0047] Ag: 0%~1.00%,

[0048] Li: 0% to 0.50%,

[0049] Na: 0% to 0.05%,

[0050] K: 0%~0.05%,

[0051] Fe: 0% to 5.00%,

[0052] Sb: 0% to 0.50%,

[0053] Pb: 0% to 0.50%,

[0054] Ba: 0% to 0.25%,

[0055] The rest: Zn and impurities,

[0056] In the cross section of the above-mentioned coating layer perpendicular to the surface of the above-mentioned steel material, the structure observed by a scanning electron microscope is as follows in terms of area fraction:

[0057] MgZn2 phase: 10% to 50%,

[0058] Total of Al phase, Al-Zn phase and Zn-Al phase: 15% to 75%,

[0059] [Al / MgZn2 / Zn ternary eutectic structure]: 0% to 65%,

[0060] The remaining part: 0% to 5.0%,

[0061] An area ratio of the total of the Al phase and the Zn—Al phase to the Al—Zn phase (([Al]+[Zn—Al]) / [Al—Zn]) is 0.8 or more.

[0062] [2] The plated steel material according to [1], wherein Si is 0.05% to 5.0% in the average chemical composition of the plating layer,

[0063] In the surface layer from the surface of the above-mentioned plating layer to a depth of 0.5 μm, the integrated value of the intensity of each element when depth analysis is performed by the GDS method satisfies the following formula (1).

[0064] IΣ(Si) / (IΣ(Zn)+IΣ(Al))≥0.005 (1)

[0065] Here, IΣ(Si), IΣ(Zn), and IΣ(Al) in formula (1) are the intensity accumulation values ​​of Si, Zn, and Al detected by the GDS method, respectively.

[0066] [3] The plated steel material according to [1] or [2], wherein in the average chemical composition of the plating layer, Ca is 0.01% to 3%,

[0067] The coating contains Ca3Al2Si2 phase, CaAl2Si2 phase, CaAl2Si2 phase, CaAl 1-x Si 1+x phase (where x = 0 to 0.2),

[0068] In the surface layer from the surface of the above-mentioned plating layer to a depth of 0.5 μm, the integrated value of the intensity of each element when depth analysis is performed by the GDS method satisfies the following formula (2).

[0069] IΣ(Ca) / IΣ(Si)≥2.0 (2)

[0070] Here, IΣ(Ca) and IΣ(Si) in the formula (2) are the intensity integration values ​​of Ca and Si detected by the GDS method, respectively.

[0071] Effects of the Invention

[0072] According to the present invention, it is possible to provide a plated steel material having excellent wet corrosion resistance and running water corrosion resistance and also excellent chemical corrosion resistance. DETAILED DESCRIPTION

[0073] Conventionally, pure Al-plated materials for use in wet and flowing water environments, such as Type 2, are known. However, Al has a weak chemical corrosion resistance, and there are problems with appearance caused by red rust generated from the end faces of the steel material. In addition, as the thickness of the steel plate increases, there is a problem that corrosion progresses significantly from the end faces, shortening the product life.

[0074] On the other hand, although Zn-Al-Mg-based plated materials have sufficient chemical corrosion protection performance and have excellent corrosion resistance compared to Zn plating in normal environments, there is a problem that corrosion products are easily lost in wet and flowing water environments, making it difficult to exert high corrosion resistance compared to normal environments.

[0075] In addition, the Zn-Al-Mg based plating layer is formed by a plurality of constituent phases. The details will be described below, but the Al phase, Al-Zn phase, Zn-Al phase, Mg2Zn phase, Mg2Zn phase 11 Phase, Zn phase, [Al / MgZn2 / Zn ternary eutectic structure] such phases and structures occupy the majority of the phase composition ratio.

[0076] The inventors of the present invention focused on the relationship between the wet corrosion resistance and running water corrosion resistance of Zn-Al-Mg based plating in a wet environment and the constituent phases and constituent structure of the plating, and conducted in-depth research. As a result, they found that the wet corrosion resistance and running water corrosion resistance can be improved by making the proportions of the constituent phases and constituent structure appropriate.

[0077] It is known that Al, a plating component, precipitates as multiple phases during solidification, namely, Al phase, Al-Zn phase, and Zn-Al phase. Among them, the Al phase has the best water resistance / flowing water resistance, but on the other hand, the chemical corrosion resistance is insufficient. In addition, although the Al-Zn phase has the highest chemical corrosion resistance among the three phases, it has poor water corrosion resistance and flowing water corrosion resistance. Furthermore, the water corrosion resistance, flowing water corrosion resistance, and chemical corrosion resistance of the Zn-Al phase are intermediate properties relative to the properties of the previous two phases.

[0078] Therefore, it is believed that if the Al phase ratio in the Zn-Al-Mg-based coating is appropriately adjusted, a plated steel material with excellent corrosion resistance can be obtained, and in-depth research has been conducted. As a result, by controlling the phase ratio in the coating layer, a plated steel material with excellent water corrosion resistance, running water corrosion resistance, and chemical corrosion resistance has been found. The steel structure manufactured by the plated steel material of the present invention becomes a steel structure with excellent water corrosion resistance, running water corrosion resistance, and chemical corrosion resistance. The following is a description of a plated steel material as an embodiment of the present invention.

[0079] The plated steel material of the present embodiment comprises a steel material and a plating layer disposed on the surface of the steel material, wherein the average chemical composition of the plating layer comprises, by mass%, Al: 10.0% to 40.0%, Mg: more than 4.0% and 8.5% or less, Si: 0% to 5.0%, Ca: 0% to 3.00%, Sn: 0% to 3.00%, Bi: 0% to 1.00%, In: 0% to 1.00%, Y: 0% to 0.50%, La: 0% to 0.5 0%, Ce: 0% to 0.50%, Sr: 0% to 0.50%, B: 0% to 1.00%, P: 0% to 0.50%, Cr: 0% to 0.25%, Ti: 0% to 0.25%, V: 0% ~0.25%, Zr: 0% ~ 0.25%, Ni: 0% ~ 1.00%, Co: 0% ~ 0.25%, Nb: 0% ~ 0.25%, Cu: 0% ~ 1.00%, Mn: 0% ~ 0.25% 、Mo: 0%~0.25%, W: 0%~0.25%, Ag: 0%~1.00%, Li: 0%~0.50%, Na: 0%~0.05%, K: 0%~0.05%, Fe: 0%~5.00%, Sb: 0%~0.50%, Pb: 0%~0.50%, Ba: 0%~0.25%, the remainder: Zn and impurities, in the cross section of the plating layer perpendicular to the surface of the steel material, using a scanning electron microscope The structure observed under the microscope is calculated by area fraction as follows: MgZn2 phase: 10% to 50%, Al phase, Al-Zn phase and Zn-Al phase in total: 15% to 75%, [ternary eutectic structure of Al / MgZn2 / Zn]: 0% to 65%, and the remainder: 0% to 5.0%. The area ratio of the total Al phase and Zn-Al phase to the Al-Zn phase (([Al] + [Zn-Al]) / [Al-Zn]) is greater than 0.8.

[0080] In addition, the plated steel material of this embodiment preferably has Si of 0.05% to 5.0% in the average chemical composition of the plating layer, and the cumulative intensity value of each element in the surface layer from the surface of the plating layer to a depth of 0.5 μm when performing a depth analysis using the GDS method satisfies the following formula (1).

[0081] IΣ(Si) / (IΣ(Zn)+IΣ(Al))≥0.005 (1)

[0082] Here, IΣ(Si), IΣ(Zn), and IΣ(Al) in formula (1) are the intensity accumulation values ​​of Si, Zn, and Al detected by the GDS method, respectively.

[0083] Furthermore, the plated steel material of the present embodiment preferably has an average chemical composition of the coating layer containing 0.01% to 3% Ca, and the coating layer contains Ca3Al2Si2 phase, CaAl2Si2 phase, CaAl2Si2 phase, CaAl1-x Si 1+x In any of the phases (where x=0 to 0.2), the integrated value of the intensity of each element in the surface layer from the surface of the plating layer to a depth of 0.5 μm satisfies the following formula (2) when depth analysis is performed by the GDS method.

[0084] IΣ(Ca) / IΣ(Si)≥2.0 (2)

[0085] Here, IΣ(Ca) and IΣ(Si) in the formula (2) are the intensity integration values ​​of Ca and Si detected by the GDS method, respectively.

[0086] In the following description, the "%" expression of the content of each element in the chemical composition means "mass %". In addition, the numerical range expressed by "to" means a range that includes the numerical values ​​recorded before and after the "to" as the lower limit and the upper limit. It should be noted that the numerical range in which the numerical values ​​recorded before and after the "to" are marked with "exceeding" or "below" means a range that does not include these numerical values ​​as the lower limit or the upper limit.

[0087] It should be noted that the so-called "corrosion resistance" refers to the property of the coating itself that it is not easy to corrode. Since the Zn-based coating has a chemical corrosion protection effect on steel, the coating corrodes and turns into white rust before the steel corrodes. After the white rusted coating disappears, the steel corrodes and produces red rust. This is the corrosion process of the plated steel sheet.

[0088] The term “chemical corrosion resistance” refers to the property of suppressing corrosion of exposed portions of steel (e.g., cut end portions of plated steel, portions of steel exposed due to cracking of hot-dip plating during processing).

[0089] Furthermore, the term “wet water corrosion resistance or flowing water corrosion resistance” refers to the property that the plating layer itself is not easily corroded when water is dropped onto the surface of the plating layer and the water flows on the plating layer.

[0090] There is no particular restriction on the material of the steel. For example, various steels can be used, such as general steel, Ni pre-plated steel, Al killed steel, ultra-low carbon steel, high carbon steel, various high-tensile steels, and some high-alloy steels (steel containing strengthening elements such as Ni and Cr, etc.). In addition, there are no particular restrictions on the conditions such as the manufacturing method of the steel and the manufacturing method of the steel plate (hot rolling method, pickling method, cold rolling method, etc.). Furthermore, the steel can also be formed with 3g / m2 of Zn, Ni, Sn or their alloys. 2 The following metal film or alloy film steel.

[0091] Next, the coating is described. The coating of the present embodiment includes a Zn-Al-Mg alloy layer. In addition, the coating may also include an Al-Fe alloy layer. The Zn-Al-Mg alloy layer to which alloy elements such as Al and Mg are added to Zn has improved corrosion resistance relative to a conventional Zn coating. For example, even if the thickness is half that of a conventional Zn coating, the Zn-Al-Mg alloy layer has the same corrosion resistance as the Zn coating. Therefore, the coating of the present embodiment also has the same or higher corrosion resistance as the Zn coating.

[0092] The Zn-Al-Mg alloy layer is formed of a Zn-Al-Mg alloy. The Zn-Al-Mg alloy is a ternary alloy containing Zn, Al, and Mg.

[0093] The Al-Fe alloy layer is an interface alloy layer between the steel material and the Zn-Al-Mg alloy layer.

[0094] That is, the coating of the present embodiment can be a single-layer structure of a Zn-Al-Mg alloy layer, or a laminated structure including a Zn-Al-Mg alloy layer and an Al-Fe alloy layer. In the case of a laminated structure, it is preferable that the Zn-Al-Mg alloy layer is set as a layer constituting the surface of the coating. In addition, an oxide film of the coating constituent elements is formed on the outermost surface of the coating with a thickness of less than about 1 μm, but since it is relatively thin relative to the overall thickness of the coating, it is mostly ignored from the main body of the coating.

[0095] The overall thickness of the coating is preferably set to 5 to 70 μm. The overall thickness of the coating is affected by the coating conditions, so the overall thickness of the coating is not limited to the range of 5 to 70 μm. The overall thickness of the coating is affected by the viscosity and specific gravity of the coating bath in the usual hot dip coating method. In addition, the overall thickness of the coating is adjusted by the drawing speed of the steel material (coated original plate) and the strength of the wiping.

[0096] Al-Fe alloy layer is formed on the surface of steel (specifically between steel and Zn-Al-Mg alloy layer), and Al5Fe2 phase is the main phase layer as organization. Al-Fe alloy layer is formed by mutual atomic diffusion of base metal (steel) and plating bath. When hot dip plating method is used as a method of manufacture, in the plating layer containing Al element, Al-Fe alloy layer is easily formed. Since Al above a certain concentration is contained in the plating bath, Al5Fe2 phase is formed at most. However, atomic diffusion needs to spend time, and there is also a part where Fe concentration becomes high in the part close to the base metal. Therefore, Al-Fe alloy layer is also likely to partially contain AlFe phase, Al3Fe phase, Al2Fe phase, etc. in small quantities. In addition, since a certain concentration of Zn is also contained in the plating bath, Zn is also contained in small quantities in the Al-Fe alloy layer.

[0097] When Si is contained in the plating layer, Si is particularly easy to be taken into the Al-Fe alloy layer, and it is possible to form an Al-Fe-Si intermetallic compound phase. As the identified intermetallic compound phase, there is an AlFeSi phase, and as isomers, there are α, β, q1, q2-AlFeSi phases. Therefore, it is possible to detect these AlFeSi phases in the Al-Fe alloy layer. The Al-Fe alloy layer containing these AlFeSi phases is also called an Al-Fe-Si alloy layer.

[0098] Next, the average chemical composition of the coating is described. When the coating is a single-layer structure of a Zn-Al-Mg alloy layer, the average chemical composition of the entire coating is the average chemical composition of the Zn-Al-Mg alloy layer. In addition, when the coating is a laminated structure of an Al-Fe alloy layer and a Zn-Al-Mg alloy layer, it is the average chemical composition of the total of the Al-Fe alloy layer and the Zn-Al-Mg alloy layer.

[0099] Usually, in hot-dip plating, because the formation reaction of coating is basically completed in plating bath, the chemical composition of Zn-Al-Mg alloy layer becomes roughly equal to plating bath. In addition, in hot-dip plating, Al-Fe alloy layer is formed and grows instantly just after plating bath is immersed. Then, Al-Fe alloy layer completes formation reaction in plating bath, and its thickness is also mostly fully small relative to Zn-Al-Mg alloy layer. Therefore, as long as special heat treatments such as heating alloying treatment are not carried out after plating, the average chemical composition of coating as a whole is substantially equal to the chemical composition of Zn-Al-Mg alloy layer, and the composition of Al-Fe alloy layer etc. can be ignored.

[0100] Al: 10.0%~40.0%

[0101] Al, like Zn, is an element constituting the main body of the coating. Although Al has a small substitutional corrosion protection effect, by containing Al in the coating, the wet corrosion resistance, running water corrosion resistance and flat surface corrosion resistance are improved. In addition, if Al is not present, Mg cannot be stably maintained in the coating bath, so it is contained in the coating bath as an indispensable element in manufacturing. The Al content is set to 10.0% or more in order to contain a large amount of Mg required for the later-described content, or to ensure a certain degree of corrosion resistance. If it is below this content, it is difficult to build a coating bath, and it becomes difficult to ensure corrosion resistance. In addition, the Al content is set to 40.0% or less because Al has a weak substitutional corrosion protection effect on the steel plate. If the content is above this, it becomes impossible to obtain sufficient substitutional corrosion resistance, so the upper limit is set to 40.0% or less.

[0102] Mg: more than 4.0% and less than 8.5%

[0103] Mg is an element that has a chemical corrosion protection effect and improves the corrosion resistance of the coating. By containing a certain amount of Mg, a MgZn2 phase is formed in the coating. The higher the Mg content in the coating, the more MgZn2 phase is formed. It is known that the MgZn2 phase adopts a structure called the Laves phase, and it is known that its hardness is high. Setting the Mg content to more than 4.0% is the concentration required for exerting corrosion resistance. When Mg is less than 4.0%, sufficient corrosion resistance cannot be obtained. In addition, the MgZn2 phase will not be fully formed in the coating, and the corrosion resistance of the coating itself will also decrease. If the Mg content becomes excessive, the manufacture of the coating becomes difficult and the processability of the coating is reduced, so the upper limit is 8.5% or less. The more preferred Mg content is 5.0% to 7.0%.

[0104] Si: 0% to 5.0%

[0105] If Si is included in the plating bath, a single Si phase or Mg2Si will be precipitated in the coating. If Ca is also included together with Si, an Al-Ca-Si compound will be precipitated. Since Si has excellent wet corrosion resistance and running water corrosion resistance, the wet corrosion resistance and running water corrosion resistance can be further improved by precipitating Si or Si-based compounds in the surface layer of the coating. Since Si is an optional added element, it can also be 0%, but if it contains more than 0.05%, the wet corrosion resistance and running water corrosion resistance are further improved. However, if Si exceeds 5.0%, a large amount of slag will be generated and unplated coating will occur frequently. Therefore, the Si concentration is 0 to 5.0%, or it can be 0.05% to 5.0%, or it can be more than 0.05% and less than 1.0%, or it can be 0.10% to 0.50%.

[0106] Ca: 0%~3.00%

[0107] Ca is easily oxidized in the atmosphere. If it exists in the plating bath, it has the effect of forming a dense oxide film on the bath surface and preventing the oxidation of Mg. Through the above effect, the Mg concentration is stabilized, making it easy to manufacture the plated steel sheet of the target composition. Since Ca is an arbitrary added element, it can also be 0%, but in order to appropriately exert the above effect, the Ca content is set to more than 0%, and more preferably set to 0.01% or more. In addition, when containing more than 0.01% Ca, it becomes easy to form Al-Ca-Si compounds or Ca-Al-Zn compounds. Among them, Al-Ca-Si compounds are excellent in water-wet corrosion resistance and running water corrosion resistance, so by concentrating these compounds in the plating surface layer, the water-wet corrosion resistance and running water corrosion resistance can be improved. The upper limit of Ca is set to 3.00% or less.

[0108] Element Group A

[0109] Sn: 0%~3.00%

[0110] Bi: 0%~1.00%

[0111] In: 0%~1.00%

[0112] The elements of element group A have the effect of improving the chemical corrosion resistance. However, there is a tendency to bind Mg more strongly than Zn, and the effect of the contained Mg becomes smaller, so there is an upper limit to the content of these elements. If the upper limit is exceeded, the adhesion of slag and the like increases, and there is a tendency for wet corrosion resistance and running water corrosion resistance, processability, and weldability to deteriorate. Therefore, Sn is set to 0-3.00%, and more preferably set to more than 0 and less than 3.00%. Bi is set to 0%-1.00%, and more preferably set to more than 0 and less than 1.00%. In is set to 0%-1.00%, and more preferably set to more than 0 and less than 1.00%.

[0113] Element Group B

[0114] Y: 0%~0.50%

[0115] La: 0%~0.50%

[0116] Ce: 0%~0.50%

[0117] Sr: 0%~0.50%

[0118] Y, La, Ce, and Sr, which are element group B, are easily oxidized in the atmosphere. If they are present in the plating bath, they have the effect of forming a dense oxide film on the bath surface and preventing the oxidation of Mg. Through the above-mentioned effect, the Mg concentration is stabilized, making it easy to manufacture the plated steel sheet of the target composition. In order to appropriately exert such an effect, the content of these elements is set to more than 0%, and more preferably to more than 0.01%. However, there is an upper limit to the content of each element. If the upper limit of the content is exceeded, there is a tendency that the construction of the plating bath becomes difficult. In addition, there is a tendency that slag and the like adhere more, and the wet corrosion resistance and running water corrosion resistance, processability, and weldability also deteriorate. Therefore, Y, La, Ce, and Sr are set to 0% to 0.50%, preferably to more than 0 and less than 0.50%, and more preferably to more than 0.01% and less than 0.50%.

[0119] Element Group C

[0120] B: 0%~1.00%

[0121] P: 0%~0.50%

[0122] B and P in element group C are semi-metallic elements. These elements generally do not affect wet corrosion resistance and running water corrosion resistance, but the content of each element has an upper limit. If the upper limit of the content is exceeded, there is a tendency for slag and the like to adhere more and the corrosion resistance to deteriorate. Therefore, B and P are set to 0% to 1.0% and 0% to 0.50%, respectively.

[0123] Element Group D

[0124] Cr: 0%~0.25%

[0125] Ti: 0%~0.25%

[0126] V: 0%~0.25%

[0127] Zr: 0%~0.25%

[0128] Ni: 0%~1.00%

[0129] Co: 0%~0.25%

[0130] Nb: 0%~0.25%

[0131] Cu: 0%~1.00%

[0132] Mn: 0%~0.25%

[0133] Mo: 0%~0.25%

[0134] W: 0%~0.25%

[0135] Ag: 0%~1.00%

[0136] Li: 0%~0.50%

[0137] Na: 0%~0.05%

[0138] K: 0%~0.05%

[0139] Fe: 0%~5.00%

[0140] Cr, Ti, V, Zr, Ni, Co, Nb, Cu, Mn, Mo, W, Ag, Li, Na, K and Fe of element group D are metal elements. These elements are taken into the plating layer to form substitution solid solution and new high melting point intermetallic compounds. As a result, wet corrosion resistance and running water corrosion resistance are improved. There is an upper limit to the content of each element. If the upper limit of the content is exceeded, there is a tendency for slag and the like to adhere more. Therefore, Na and K are set to 0% to 0.05%, preferably more than 0% and less than 0.05%. Cr, Ti, V, Zr, Co, Nb, Mn, Mo, and W are set to 0% to 0.25%, preferably more than 0% and less than 0.25%. Li is set to 0% to 0.50%, preferably more than 0% and less than 0.50%. Ni, Cu, and Ag are set to 0% to 1.00%, preferably more than 0% and less than 1.00%. Furthermore, Fe may be inevitably contained in the plating layer because it may diffuse from the base metal into the plating layer during plating production. Therefore, the Fe content is 0% to 5.00%, and may be more than 0% and less than 5.00%.

[0141] Element Group E

[0142] Sb: 0%~0.50%

[0143] Pb: 0%~0.50%

[0144] Ba: 0%~0.25%

[0145] Sb, Pb, and Ba, which are element group E, are elements with properties similar to those of Zn. Therefore, although the inclusion of these elements does not exert a special effect, it has an effect such as making it easier to form zinc flower patterns in the appearance of the coating. However, if they are contained in excessive amounts, the corrosion resistance may be reduced. Therefore, Sb and Pb are set to 0% to 0.50%, preferably more than 0% and less than 0.50%. Ba is set to 0% to 0.25%, preferably more than 0% and less than 0.25%.

[0146] The rest: Zn and impurities

[0147] Zn is a metal with a low melting point, and exists as the main phase of the coating on the steel. Zn is an element required to ensure corrosion resistance and obtain the chemical protection effect on the steel. Zn is set to the remainder, but it is preferably contained at 50.00% or more. If Zn is less than 50.00%, it is possible that the main body of the metal structure of the Zn-Al-Mg alloy layer becomes the Al phase, and the Zn phase that exhibits chemical protection is insufficient. It is more preferably set to 65.00% or more or 70.00% or more. It should be noted that the upper limit of the Zn content is the amount of the remainder excluding elements and impurities other than Zn.

[0148] In addition, impurities in the coating refer to components contained in the raw materials or components mixed in during the manufacturing process, and are components not intentionally contained. For example, in the coating, components other than Fe may be mixed in trace amounts as impurities due to mutual atomic diffusion between the steel material (base metal) and the coating bath.

[0149] For the identification of the average chemical composition of the coating, the coating is stripped and dissolved with an acid containing an inhibitor that inhibits corrosion of the base metal (steel) to obtain an acid solution. Then, the chemical composition can be obtained by measuring the obtained acid solution using ICP emission spectrometry or ICP-MS. There is no particular restriction on the acid species as long as it can dissolve the coating. If the area and weight before and after stripping are measured, the coating adhesion amount (g / m 2 ).

[0150] Next, the microstructure of the coating will be described.

[0151] The proportion of the phases and structures contained in the coating has a great influence on the wet corrosion resistance and running water corrosion resistance of the plated steel. Even for coatings with the same composition, the phases or structures contained in the metal structure change according to different manufacturing methods, and the properties become different. The confirmation of the metal structure of the coating can be easily confirmed by a scanning electron microscope (SEM-EDS) with an energy dispersive X-ray analyzer. In any vertical cross-section of the coating after mirror finishing, for example, by obtaining a reflected electron image, the state of the approximate metal structure of the coating can be confirmed. The so-called vertical cross-section of the coating refers to a cross-section in the thickness direction of the coating perpendicular to the surface of the steel. Since the thickness of the coating of the present embodiment is 3 to 80 μm, preferably 5 to 70 μm, it is preferred to confirm its metal structure in the SEM with a field of view of 500 to 5000 times. The lower limit of the thickness of the coating is set to 3 μm or more because it may be difficult to ensure corrosion resistance when the thickness is lower than this. In addition, the upper limit of the coating thickness is set to 80 μm because: if the thickness exceeds this, there may be concerns about peeling of the coating when processing the plated steel, which may not be practical. For example, when a coating with a thickness of 25 μm is confirmed at a magnification of 2000 times, it can be confirmed that each field of view is 25 μm (coating thickness) × 40 μm (SEM field width) = 1000 μm 2 In the present embodiment, since it is possible to observe a local field of view of the SEM field of view of the coating, in order to obtain the average information of the coating, it is sufficient to select 25 points of the field of view from any cross section as the average information. 2The metal structure in the field of view can be observed to determine the phase or area ratio of the metal structure constituting the coating.

[0152] The reflected electron image obtained by SEM is preferred in that the phases or structures contained in the coating can be easily identified. Since elements with small atomic numbers such as Al are imaged darker, and elements with large atomic numbers such as Zn are imaged whiter, the ratio of these structures can be easily read.

[0153] In order to confirm each phase, in EDS analysis, accurately confirm the composition of the phase, read roughly the same component phase by element mapping (mapping) etc. to determine the phase. EDS analysts can be used to distinguish the phases of roughly the same composition by performing element mapping. If the phases of roughly the same composition can be determined, the area of ​​its crystalline phase in the observation field can be known. If the area is grasped, the equivalent circle diameter is obtained by calculation, and the average crystal grain size can be calculated.

[0154] In addition, the area ratio of each phase in the observation field can be obtained. The area ratio of a specific phase in the plating layer is equivalent to the volume ratio of the phase in the plating layer.

[0155] Al phase

[0156] The Al phase in the present embodiment is an area where the Al content exceeds 35% by mass in the coating. Zn may also be included in the Al phase, but the Zn content is less than 65%. The Al phase can be clearly distinguished from other phases and structures in the SEM reflection electron image. That is, the Al phase is displayed in the darkest in the SEM reflection electron image in most cases. In the present embodiment, the Al phase takes various forms such as the situation where it appears as a block-shaped or circular and flat tree-shaped cross section in any cross section. It should be noted that in the present embodiment, the Al contained in the [ternary eutectic structure of Al / MgZn2 / Zn] is not included in the Al phase. The Al phase has excellent water-wet corrosion resistance and running water corrosion resistance. The Al in the bath is precipitated as the Al phase and the Al-Zn phase and Zn-Al phase described later, but from the aspect of ensuring water-wet corrosion resistance and running water corrosion resistance, it is preferably precipitated as the Al phase.

[0157] Al-Zn phase

[0158] The Al-Zn phase in the present embodiment is a phase containing 65 to 75% by mass of Zn and Al. The Al-Zn phase is an aggregate of a fine Zn phase (hereinafter referred to as a fine Zn phase) with a particle size of about 1 μm and a fine Al phase (hereinafter referred to as a fine Al phase) with a particle size of less than 1 μm. In the molten coating, Al has a structure different from the crystal structure at room temperature, and becomes able to dissolve a large amount of Zn phase, and exists as a high-temperature stable phase containing the Zn phase. On the other hand, at room temperature, the content of the Zn phase in the high-temperature stable phase is extremely reduced, and Al and Zn are balanced and separated to exist as an Al-Zn phase containing a fine Al phase and a fine Zn phase. That is, the Al-Zn phase is a phase containing a fine Zn phase at a ratio of 65 to 75% by mass. The Al-Zn phase is a phase with a composition equivalent to the β phase in the Al-Zn phase diagram, and is distinguished from the Al phase and the Zn-Al phase contained in the coating in terms of properties by reflection electron SEM images and wide-angle X-ray diffraction. Therefore, in the present embodiment, a phase with an Al component of 25 to 35 mass % and a Zn component of 65 to 75 mass % is defined as the Al-Zn phase.

[0159] In addition, the Al-Zn phase is inferior to the Al phase and the Zn-Al phase in wet corrosion resistance and running water corrosion resistance. Therefore, in order to ensure the running water resistance of the coating, it is preferred to make the Al-Zn phase as non-crystallized as possible. Therefore, the relationship between the area ratios of the Al-Zn phase, the Al phase, and the Zn-Al phase in the structure needs to satisfy the following formula (A).

[0160] ([Al]+[Zn-Al]) / [Al-Zn]≥0.8(A)

[0161] In formula (A), [Al] is the area ratio (%) of the Al phase, [Zn-Al] is the area ratio (%) of the Zn-Al phase, and [Al-Zn] is the area ratio (%) of the Al-Zn phase.

[0162] Zn-Al phase

[0163] The Zn-Al phase in the present embodiment is a phase containing 75 to 85% by mass of Zn and Al. The Zn-Al phase is an aggregate of a fine Zn phase (hereinafter referred to as a fine Zn phase) with a particle size of about 1 μm and a fine Al phase with a particle size of less than 1 μm. The β phase, which is a high-temperature stable phase, separates into Zn and Al phases below 250°C, but at this time, it takes in the surrounding Zn to form a Zn-Al phase. Although the Zn-Al phase is inferior to the Al phase, it has excellent water corrosion resistance and running water corrosion resistance compared to the Al-Zn phase. In addition, if the Al concentration in the plating bath is less than 15%, it is difficult for the Al phase to precipitate, so by controlling the precipitation of the Zn-Al phase, the water corrosion resistance and running water corrosion resistance can be improved.

[0164] In order to improve the wet corrosion resistance, running water corrosion resistance, and ensure the chemical corrosion resistance, the total area fraction of the Al phase, Al-Zn phase, and Zn-Al phase needs to be set to 15% to 75%. It should be noted that it is not necessary to crystallize all of the Al phase, Al-Zn phase, and Zn-Al phase, and any one of the phases may be 0%.

[0165] MgZn2 phase

[0166] The MgZn2 phase of the present embodiment is a region where Mg is 11 to 21 mass %, preferably 16 mass %, and Zn is 81 to 89 mass %, preferably 84 mass % in the coating. The MgZn2 phase is often photographed in a gray intermediate color between Al and Zn in a reflected electron image of a SEM. In a reflected electron image of a SEM, the MgZn2 phase can be clearly distinguished from an Al-Zn phase, an Al phase, and a ternary eutectic structure of Al / MgZn2 / Zn.

[0167] Compared with the Al phase, the MgZn2 phase has higher chemical corrosion resistance, but on the other hand, it has poor water corrosion resistance and running water corrosion resistance. Therefore, from the perspective of chemical corrosion resistance, the more MgZn2 phases, the better. However, on the other hand, if the MgZn2 phases become more, the water corrosion resistance and running water corrosion resistance will decrease, so there is an upper limit to the area ratio of the MgZn2 phase. The proportion of the MgZn2 phase in the coating needs to achieve a balance between the two characteristics, so the area ratio of the MgZn2 phase needs to be set to 10% to 50%.

[0168] [Ternary eutectic structure of Al / MgZn2 / Zn]

[0169] [Ternary eutectic structure of Al / MgZn2 / Zn] is a eutectic structure including Al phase, MgZn2 phase and Zn phase, and is clearly distinguished from the MgZn2 phase included as the main phase of the coating and the above-mentioned Al phase in the reflected electron image of the SEM.

[0170] By allowing the [ternary eutectic structure of Al / MgZn2 / Zn] containing a Zn phase to exist to a certain extent, it is possible to ensure chemical corrosion resistance and improve end face corrosion resistance. On the other hand, since the wet corrosion resistance and running water corrosion resistance are reduced, if the wet corrosion resistance and running water corrosion resistance are taken into consideration, the upper limit of the area ratio of the [ternary eutectic structure of Al / MgZn2 / Zn] is set to 65 area% or less, preferably 40 area% or less. There is no particular restriction on the lower limit of the area ratio of the [ternary eutectic structure of Al / MgZn2 / Zn], and it can also be set to 0%.

[0171] Mg2Si phase

[0172] When Si is included in the coating, Si may be precipitated as Mg2Si phase. Since the Mg2Si phase has excellent water corrosion resistance and running water corrosion resistance, if the Mg2Si phase exists in the surface layer, it acts as a barrier layer for water and has the effect of suppressing the consumption of the coating. Therefore, it is preferred to precipitate Mg2Si in the surface layer.

[0173] The presence of Mg2Si can be confirmed by X-ray diffraction measurement. It can be determined by the following method: in the X-ray diffraction measurement, whether the diffraction peak of the Mg2Si phase appears in the X-ray diffraction pattern of the coating surface obtained by measuring using Cu-Kα rays under the conditions of X-ray output of 50 kV and 300 mA. There is no particular limitation on the X-ray diffraction device, but for example, the sample horizontal type strong X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. can be used.

[0174] The concentration of Si in the surface layer of the coating can be confirmed by GDS (glow discharge luminescence analysis). For the improvement of water corrosion resistance and running water corrosion resistance, it is preferable that Si compounds exist in the surface layer of the coating. Specifically, it is preferable that Si exists in the range from the surface of the coating to a depth of 0.5 μm. In order to convert the depth direction by GDS, it can be derived from the relationship between the sputtering seconds of Zn and the depth. The amount of Si required to improve water corrosion resistance and running water corrosion resistance can be grasped by comparing the intensity ratio with Al and Zn as the main components. Specifically, when the intensity cumulative value of element X during GDS measurement from the surface of the coating to a depth of 0.5 μm is set to IΣ(X), it is preferable to satisfy the following formula (1). As a result, water corrosion resistance and running water corrosion resistance are further improved.

[0175] It should be noted that the intensity accumulation value of the element X shown in the present invention refers to the intensity in the coating, and does not include the intensity accumulation value of the coating film and the chemical conversion treatment film. In order to confirm the GDS intensity accumulation value of the coating of the plated steel material that has been coated or chemically converted, it is sufficient to remove the coating film or the chemical conversion treatment film or both by chemical treatment, grinding, etc., and then use GDS to measure. In the case where it is difficult to remove the film, the surface of the coating is defined according to the GDS measurement results. Specifically, GDS is used to measure from the surface of the plated steel material to the steel material, and for the intensity of the coating main components of the present invention, namely Zn, Al, and Mg, the first position where the above-mentioned total element intensity meets more than 1 / 3 of the respective peak intensity values ​​is regarded as the coating surface.

[0176] It should be noted that IΣ(Si), IΣ(Zn) and IΣ(Al) in the following formula (1) are the integrated values ​​of the intensities of Si, Zn and Al detected by the GDS method in the range from the surface of the plating layer to a depth of 0.5 μm.

[0177] IΣ(Si) / (IΣ(Zn)+IΣ(Al))≥0.005 (1)

[0178] It should be noted that the intensity of Si appears as a peak in the range from the surface of the coating to a depth of 0.5 μm and at the interface between the coating and the steel material. The peak intensity of Si on the surface side of the coating is more than 5 times the intensity of Si at a position 1 / 2 of the thickness of the coating compared to the intensity.

[0179] Al-Ca-Si phase

[0180] If Ca and Si are contained in the plating bath, Al-Ca-Si phase is precipitated as Si compound in the plating layer. Specifically, Al-Ca-Si phase, Ca3Al2Si2 phase, Ca ... 1-x Si 1+x Phase (where x = 0 to 0.2) is precipitated. Compared with the above-mentioned Mg2Si phase, the Al-Ca-Si phase has better water corrosion resistance and running water corrosion resistance. Therefore, if the Al-Ca-Si phase exists in the range from the surface of the coating to a depth of 0.5 μm, it acts as a barrier layer for water and has the effect of suppressing the consumption of the coating. More specifically, it is preferred to satisfy the following formula (2).

[0181] In the following formula (2), IΣ(Ca) and IΣ(Si) are respectively the integrated values ​​of the intensities of Ca and Si detected by the GDS method in the range from the surface of the plating layer to a depth of 0.5 μm.

[0182] IΣ(Ca) / IΣ(Si)≥2.0 (2)

[0183] The above phases and structures constitute the main phase of the coating, and they account for more than 90% of the area fraction of the coating. On the other hand, other metal phases are formed by containing elements other than Zn, Mg and Al in the coating. Among them, although they have an effect on water resistance, water resistance and corrosion resistance, their influence is not significant. According to the composition of the coating, it is difficult to set the remaining part to more than 5.0 area%, so it becomes less than 5.0 area%. The remaining part can also be 0%.

[0184] The method for determining the area ratio of the phase and structure in the coating is as described above. The cross section of the coating in the thickness direction perpendicular to the surface of the steel material is exposed, and the metal structure is confirmed at a viewing angle of 500 to 5000 times. 25 points of the viewing angle are selected from any cross section as the average information. That is, for a total of 25000μm 2 The metal structure in the field of view is observed to determine the phase or area ratio of the metal structure constituting the coating. In order to confirm each phase, in EDS analysis, the composition of the phase is accurately confirmed, and roughly the same component phase is read by element mapping to determine the phase. EDS analysts can use element mapping to distinguish phases of roughly the same composition. If the phase of roughly the same composition can be determined, the area of ​​its crystalline phase in the observation field can be known. If the area is grasped, the equivalent circle diameter is calculated, thereby the average crystal grain size can be calculated, and the area ratio of each phase in the observation field can be obtained.

[0185] In the case of performing a composition analysis in the depth direction of the inside of the coating by GDS analysis, a glow discharge luminescence spectrometer (GDS) is used. For example, as a glow discharge luminescence spectrometer, LECO Japan 850A can also be used, but the measuring device is not limited to this. The analysis conditions for the case of performing a depth analysis by argon sputtering are set as follows: argon pressure: 0.27MPa, output power: 30W, output voltage: 1000V, discharge area: within a circular area with a diameter of 4mm. The GDS analysis is performed by etching from the surface of the coating toward the depth direction to a depth of 0.5μm, and the cumulative value of the luminescence intensity of each element can be obtained. Based on this cumulative value, it is determined whether the above conditions (1) and (2) are met.

[0186] In addition, Al-Ca-Si phase (Ca3Al2Si2 phase, CaAl2Si2 phase, CaAl2Si2 phase, CaAl 1-x Si 1+x In addition to SEM and ESD measurements, the presence of Al-Ca-Si phase can also be confirmed by X-ray diffraction measurement. Its presence can be confirmed by the following method: In the X-ray diffraction measurement, whether the diffraction peak of the Al-Ca-Si phase appears in the X-ray diffraction pattern of the coating surface obtained by measuring with Cu-Kα rays under the conditions of X-ray output of 50 kV and 300 mA. There is no particular limitation on the X-ray diffraction device, but for example, the sample horizontal type strong X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. can be used, but it is not limited to this.

[0187] The presence of Mg2Si can be confirmed by X-ray diffraction measurement in addition to SEM and ESD measurement. In the X-ray diffraction measurement, Cu-Kα rays are used, and the measurement is performed under the conditions of X-ray output of 50 kV and 300 mA. Its presence can be confirmed by the following method: whether the diffraction peak of the Mg2Si phase appears in the X-ray diffraction pattern on the surface of the coating. As an X-ray diffraction device, for example, a sample horizontal type strong X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. can be used, but it is not limited to this.

[0188] Next, a method for producing a plated steel material according to an embodiment of the present invention will be described. The plated steel material according to the present embodiment can be produced by either an immersion hot dip coating method (batch hot dip coating method) or a continuous hot dip coating method.

[0189] The size, shape, surface morphology, etc. of the steel material to be plated are not particularly limited. Even ordinary steel materials, high-tensile steel, stainless steel, etc., as long as they are steel materials, can be applied. More specifically, for example, various steel materials such as general steel, Ni pre-plated steel, Al killed steel, ultra-low carbon steel, high carbon steel, various high-tensile steels, and some high-alloy steels (steel containing strengthening elements such as Ni and Cr, etc.) can be applied. Steel strips of general structural steel are most preferred.

[0190] For steel materials, the surface can be finished by shot peening, grinding brush, etc. in advance to make the surface adhere with Ni plating, Zn plating, Sn plating, etc. 3g / m 2 The following metal film or alloy film can be plated without any problem. In addition, as a preliminary treatment of the steel material, it is preferred to fully wash the steel material by degreasing and pickling.

[0191] After the steel material surface is fully heated and reduced by a reducing gas such as H2, the steel material is immersed in a plating bath prepared with a predetermined composition. For high-tensile steel, the atmosphere during annealing is generally humidified, and the internal oxidation method is used to ensure the plating adhesion of high-Si and Mn steels. By performing such a treatment, unplated plated steel materials with few appearance defects can be plated in the same way as ordinary general steel materials. Such steel materials are observed to have a fine steel surface and internal oxide film layer of a grain system on the base metal side, but they do not affect the performance of the present invention.

[0192] In the case of hot-dip plating, the composition of the coating layer can be controlled by the composition of the coating bath. The coating bath is prepared by mixing pure metals in predetermined amounts, for example, by melting in an inert atmosphere to produce an alloy of the coating bath components.

[0193] The steel material whose surface is reduced is immersed in a plating bath maintained at a predetermined concentration to form a plating layer having substantially the same composition as the plating bath. When the immersion time is prolonged and it takes a long time until solidification is completed, the formation of the interface alloy layer becomes active, so the Fe concentration may also increase. However, when the temperature is lower than 500°C, the reaction with the plating layer slows down rapidly, so the Fe concentration contained in the plating layer is usually limited to less than 5.00%.

[0194] In order to form a hot-dip coating, it is preferred to keep the coating bath at 450°C to 550°C. Then, it is preferred to immerse the reduced steel for a few seconds. On the surface of the reduced steel, Fe may diffuse into the coating bath and react with the coating bath to form an interface alloy layer (mainly an Al-Fe alloy layer) at the interface between the coating and the steel. When the interface alloy layer is formed, the steel below the interface alloy layer and the coating above are more firmly bonded in terms of metal chemistry.

[0195] After the steel is immersed in the plating bath for a specified time, it is picked up from the plating bath and the metal attached to the surface is molten by N2 wiping, thereby adjusting the plating layer to a specified thickness. The thickness of the plating layer is preferably adjusted to 3 to 80 μm. If converted to the amount of plating attached, it becomes 10 to 500 g / m 2 (single side). In addition, the thickness of the plating layer can be adjusted to 5 to 70 μm. If converted into the adhesion amount, it becomes about 20 to 400 g / m 2 (Single-sided).

[0196] After adjusting the amount of coating, the attached molten metal is solidified. The cooling means for solidifying the molten metal may be nitrogen, air, or a mixed gas of hydrogen and helium, mist cooling, or water immersion. Mist cooling is preferred, and mist cooling containing water in nitrogen is preferred. The cooling rate can be adjusted by the water content in the mist.

[0197] Under normal coating solidification conditions, for example, cooling at an average cooling rate of 5 to 20°C / second between the coating bath temperature and 150°C, the microstructure may not be controlled, and thus it may become difficult to meet the specified performance. Therefore, the cooling conditions for obtaining the coating of this embodiment are described below. As described below, under the present cooling conditions, it is preferred to adjust the average cooling rate for each temperature range.

[0198] Average cooling rate between bath temperature and 380°C: 10°C / sec to 20°C / sec

[0199] Between the bath temperature and 380°C, Si compounds are precipitated in the presence of Si. If the cooling rate is fast, the solidification of the coating progresses without sufficient Si precipitation, and there is a tendency for Si to be evenly dispersed in the coating. On the other hand, if the cooling rate is slow, the Si compounds coarsen, Si concentrates at the interface between the coating and the steel material, and there is a tendency for less Si compounds to be precipitated in the surface layer of the coating. Therefore, in order to precipitate Si compounds in the surface layer, it is necessary to set the average cooling rate between the bath temperature and 380°C to 10°C / second to 20°C / second. It should be noted that even if Si is not contained in the coating, it is advisable to set the average cooling rate between the bath temperature and 380°C to 10°C / second to 20°C / second. The preferred lower limit of the average cooling rate is 15°C / second, and the preferred upper limit is 20°C / second. By setting the average cooling rate to above the preferred lower limit, Si compounds tend to concentrate on the surface, and the MgZn2 structure is refined, so that the processability tends to be improved. By setting the average cooling rate to be below the preferred upper limit, Si compounds tend to concentrate on the surface, and the precipitation of Mg2Zn in the case of a large degree of supercooling can be suppressed. 11 The precipitation of can achieve the effect that the processability tends to be improved.

[0200] Average cooling rate between 380℃~250℃: more than 20℃ / second

[0201] Between 380°C and 250°C, the Al phase precipitates from the liquid phase of the molten metal attached to the steel material, and causes a ternary eutectic reaction of the Zn-Al-MgZn2 phase, and finally the liquid phase disappears so that the coating is completely solidified. In addition, in the temperature range between 400°C and 300°C, the Al phase changes to the Al-Zn phase as a high-temperature stable phase, that is, the Zn phase formed as the [ternary eutectic structure of Al / MgZn2 / Zn] in the precipitated Al phase is absorbed, and the [ternary eutectic structure of Al / MgZn2 / Zn] is reduced. In order to improve the wet corrosion resistance and running water corrosion resistance, the average cooling rate between 380°C and 250°C is set to at least 20°C / second. It is more preferred to set the average cooling rate to 30°C / second or more. By setting the average cooling rate to 30°C / second or more, the area ratio of the Al phase tends to increase. That is, the average cooling rate between 380° C. and 250° C. is preferably faster than the average cooling rate between the bath temperature and 380° C. The upper limit of the average cooling rate is not particularly limited, but may be, for example, 50 / sec.

[0202] Average cooling rate between 250℃ and 150℃: less than 20℃ / second

[0203] The Al-Zn phase is unstable in the temperature range of 250°C to 150°C, and is separated into the Zn phase and the Al phase. That is, the Al-Zn phase transforms into the Al phase or the Zn-Al phase. Therefore, in order to improve the wet water corrosion resistance and the running water corrosion resistance, it is preferably cooled slowly in this temperature range to promote the precipitation of the Al phase. Therefore, the cooling rate between 250 and 150°C is set to 20°C / second or less. As a result, the Al-Zn phase is separated into the Al phase and the Zn phase, and the phase transforms into the Al phase or the Zn-Al phase. This tendency becomes stronger especially when the Al concentration is high. It is more preferably set to 10°C / s or less, and more preferably set to less than 5°C / s. By setting the average cooling rate to 10°C / s or less, the area ratio of the Al-Zn phase is reduced, and good wet water corrosion resistance and running water corrosion resistance can be stably obtained. The lower limit of the average cooling rate is not particularly limited, but it can also be 2.5°C / s. If the average cooling rate is lower than 2.5°C, the MgZn2 phase in the coating structure will coarsen and the workability will tend to deteriorate.

[0204] Average cooling rate in the temperature range below 150°C

[0205] The average cooling rate in the temperature range below 150° C. during the solidification process does not affect the constituent phases in the coating layer and therefore does not need to be particularly limited, and natural cooling may be used.

[0206] By cooling under the above conditions, the plating layer of the present embodiment is formed.

[0207] After the coating is cooled, various chemical conversion treatments and coating treatments may be performed. In addition, in order to further improve the corrosion resistance, repairs such as correction coating and spraying treatment may be performed on welded parts and processed parts.

[0208] For the plated steel material of this embodiment, a film may also be formed on the plated layer. The film may be formed into one layer or two or more layers. As the type of the film directly above the plated layer, for example, a chromate film, a phosphate film, and a chromate-free film may be listed. The chromate treatment, phosphate treatment, and chromate-free treatment for forming these films may be performed by known methods. However, most of the chromate treatments may deteriorate the weldability on the surface of the plated layer, so the thickness thereof is preferably set to less than 1 μm.

[0209] There are the following types of chromate treatment: electrolytic chromate treatment in which a chromate film is formed by electrolysis; reactive chromate treatment in which a film is formed by reaction with a raw material and then excess treatment liquid is washed away; and coating chromate treatment in which a treatment liquid is applied to a coated object and dried without washing to form a film. Any of these treatments may be used.

[0210] Examples of the electrolytic chromate treatment include electrolytic chromate treatment using chromic acid, silica sol, resin (phosphoric acid, acrylic resin, vinyl ester resin, vinyl acetate acrylic emulsion, carboxylated styrene butadiene latex, diisopropanolamine-modified epoxy resin, etc.), and hard silica.

[0211] Examples of the phosphate treatment include zinc phosphate treatment, calcium zinc phosphate treatment, and manganese phosphate treatment.

[0212] Chromate-free treatment is particularly environmentally friendly and is therefore preferred. There are the following types of chromate-free treatment: electrolytic chromate-free treatment that forms a chromate-free film by electrolysis; reactive chromate-free treatment that forms a film by reaction with the raw material and then rinses away excess treatment liquid; and coating chromate-free treatment that forms a film by applying the treatment liquid to the object and drying it without washing with water. Any of these treatments may be used.

[0213] Furthermore, on the film just above the plating layer, there may also be one or more layers of organic resin films. The organic resin is not limited to a specific type, and examples thereof include polyester resins, polyurethane resins, epoxy resins, acrylic resins, polyolefin resins, or modified forms of these resins. The so-called modified form here refers to a resin obtained by reacting the reactive functional groups contained in the structures of these resins with other compounds (monomers, crosslinking agents, etc.) containing functional groups that can react with the functional groups in the structures.

[0214] As such an organic resin, one or more organic resins (unmodified resins) may be mixed and used, or one or more organic resins obtained by modifying at least one other organic resin in the presence of at least one organic resin may be mixed and used. In addition, any coloring pigment or rust-proof pigment may be included in the organic resin film. A water-based resin may also be used by dissolving or dispersing in water.

[0215] Example

[0216] The original plate of the plated steel material is set to be an original plate cut out of a cold-rolled steel plate with a thickness (t) of 3.2 mm and a thickness (t) of 0.8 mm in a size of 180 mm × 100 mm. All are SS400 (general steel). An intermittent hot-dip simulation device (manufactured by RHESCA) is used, and a K thermocouple is installed on a part of the steel plate. In a reducing atmosphere of N2 containing 5% H2, annealing is performed at 800°C to fully reduce the surface of the steel plate, and then immersed in a plating bath of various compositions for 3 seconds, and then picked up, and the plating thickness is adjusted to 10 to 30 μm by wiping with N2 gas. Among them, in Examples 55 to 58, the plating thickness is set to 3 μm, 5 μm, 70 μm, and 80 μm. The plating thickness of the front and back of the original plate is the same. After being picked up from the plating bath, the plated steel material is manufactured under various cooling conditions A to F as follows.

[0217] The average chemical composition of the coating is measured as follows. The coating is stripped and dissolved with an acid containing an inhibitor for inhibiting corrosion of the base metal (steel) to obtain an acid solution. Then, the obtained acid solution is measured by ICP emission spectrometry or ICP-MS to obtain the average chemical composition of the coating.

[0218] Condition A: After the steel material is taken out of the coating bath, the average cooling rate between the bath temperature and 150° C. is set to a value lower than 5° C. / sec (comparative condition).

[0219] Condition B: After the steel material is taken out of the coating bath, the average cooling rate between the bath temperature and 150° C. is set to a value between 5° C. and 20° C. / sec (comparative condition).

[0220] Condition C: After the steel material is taken out of the coating bath, the average cooling rate between the bath temperature and 150° C. is set to a value of 20° C. / sec or more (comparative condition).

[0221] Condition D: After the steel material is taken out of the plating bath, the average cooling rate between the bath temperature and 380°C (range T1) is set to a value between 10°C / second and 20°C / second, the average cooling rate between 380°C and 250°C (range T2) is set to a value between 20°C / second and 50°C / second, and the average cooling rate between 250°C and 150°C (range T3) is set to a value lower than 5°C / second (preferred condition). Therefore, in condition D, the average cooling rate is adjusted for each temperature range.

[0222] Condition D-2: After the steel material is taken out of the plating bath, the average cooling rate between the bath temperature and 380°C (range T1) is set to a value between 10°C / second and 20°C / second, the average cooling rate between 380°C and 250°C (range T2) is set to a value between 20°C / second and 50°C / second, and the average cooling rate between 250°C and 150°C (range T3) is set to a value below 10°C / second. Therefore, in condition D-2, the average cooling rate is adjusted for each temperature range.

[0223] Condition E: After the steel material is taken out of the coating bath, the average cooling rate between the bath temperature and 380°C (range T1) is set to a value lower than 10°C / second, the average cooling rate between 380°C and 250°C (range T2) is set to a value higher than 20°C / second and 50°C / second, and the average cooling rate between 250°C and 150°C (range T3) is set to a value lower than 5°C / second (comparative condition). Therefore, in condition E, the average cooling rate is adjusted for each temperature range.

[0224] Condition F: After the steel material is taken out of the plating bath, the average cooling rate between the bath temperature and 380°C (range T1) is set to a value of 20°C / second or more, the average cooling rate between 380°C and 250°C (range T2) is set to a value lower than 20°C / second, and the average cooling rate between 250°C and 150°C (range T3) is set to a value of 5°C / second or more (comparison condition). Therefore, in condition F, the average cooling rate is adjusted for each temperature range.

[0225] The method for determining the area ratio of the phases and structures (MgZn2 phase, Al-containing phase, [ternary eutectic structure of Al / MgZn2 / Zn], Mg2Si phase, Al-Ca-Si phase, and the remainder) in the coating is as described above. The cross section in the thickness direction of the coating perpendicular to the surface of the steel material is exposed, and the metal structure is confirmed at a viewing field of 500 to 5000 times. Specifically, the total area of ​​25000 μm 2 The metal structure in the field of view is observed to determine the phase or area ratio of the metal structure constituting the coating. In order to confirm each phase, the composition of the phase is accurately confirmed in EDS analysis, and the phase is determined by reading the roughly equivalent component phase by element mapping, etc. Element mapping can be used to distinguish phases with roughly the same composition.

[0226] The presence of Mg2Si was also confirmed by X-ray diffraction measurement. The determination was made by the following method: In the X-ray diffraction measurement, whether the diffraction peak of the Mg2Si phase appeared in the X-ray diffraction pattern of the coating surface obtained by measuring using Cu-Kα rays under the conditions of X-ray output of 50 kV and 300 mA. As the X-ray diffraction device, a sample horizontal type high-power X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. was used.

[0227] IΣ(Si) / (IΣ(Zn)+IΣ(Al)) and IΣ(Ca) / IΣ(Si) are measured by GDS analysis of the coating in the depth direction. Specifically, the analysis conditions for the depth analysis using argon sputtering are set as follows: argon pressure: 0.27MPa, output power: 30W, output voltage: 1000V, discharge area: within a circular area with a diameter of 4mm. The cumulative intensity values ​​of Si, Zn, and Al when GDS measurement is performed while etching from the surface of the coating to a depth of 0.5μm are obtained, and IΣ(Si) / (IΣ(Zn)+IΣ(Al)) and IΣ(Ca) / IΣ(Si) are calculated.

[0228] Al-Ca-Si phase (Ca3Al2Si2 phase, CaAl2Si2 phase, CaAl2Si2 phase, CaAl 1-x Si 1+x Phase) is confirmed by X-ray diffraction measurement. The following method is used to distinguish whether the diffraction peak of the Al-Ca-Si phase appears in the X-ray diffraction pattern of the coating surface obtained by measuring with Cu-Kα rays under the conditions of X-ray output of 50 kV and 300 mA. As an X-ray diffraction device, a sample horizontal type high-power X-ray diffraction device RINT-TTR III manufactured by Rigaku Co., Ltd. is used.

[0229] (Evaluation of chemical corrosion resistance)

[0230] The test material with a thickness (t) of 3.2 mm was cut into 120 mm × 50 mm, and one end face in contact with the bracket was painted. Without curing the other cut end faces, the chemical corrosion resistance was evaluated by implementing the JASO M609 test. In the combined cycle test, the red rust generation condition of the flat surface was confirmed. Red rust generation was set when the red rust area ratio was 5% or more.

[0231] The evaluation of chemical corrosion resistance was performed as follows: "B" was set as unacceptable, and "A" to "S" were set as acceptable.

[0232] Red rust was observed below 200 cycles: "B"

[0233] The case of red rust at 200 cycles: "A"

[0234] When red rust occurs at more than 200 and less than 350 cycles: "AA"

[0235] When red rust occurs at more than 350 and less than 500 cycles: "AAA"

[0236] No red rust at 500 cycles: "S"

[0237] (Evaluation of wet corrosion resistance and running water corrosion resistance)

[0238] The sample was cut into 120 mm × 60 mm pieces with a thickness (t) of 0.8 mm, and a vinyl sheet was pasted to make a flow path with a width of 20 mm and a length of 100 mm as a sample. The sample was set at an inclination of 15° from the horizontal, and artificial rainwater (according to the Cl - :10ppm, SO4 2- :40ppm, NO3 - : 20ppm concentration. Further add NaOH aqueous solution to adjust to pH = 5). The dripping is adjusted to 100-200μl each time. The case where red rust is observed in more than 5% of the flow path area is set as the occurrence of red rust, and the evaluation is performed as follows until the red rust occurs. Regarding the pass or fail of water corrosion, the following "B" is set as unqualified, and "A" to "S" are set as qualified.

[0239] In case of red rust at less than 8 weeks: "B"

[0240] If red rust occurs after more than 8 weeks and less than 12 weeks: "A"

[0241] If red rust occurs after 12 weeks or more and less than 14 weeks: "AA"

[0242] If red rust occurs at a period of more than 14 weeks and less than 16 weeks: "AAA"

[0243] No red rust after 16 weeks: "S"

[0244] (Processability Evaluation)

[0245] The test material with a plate thickness (t) of 0.8 mm was cut into 30 mm × 100 mm, and subjected to 2t 180° bending (a test of 180° bending with a spacer twice the thickness of the plate inserted), and then bent back to make it flat, and a transparent tape (registered trademark, Japanese: セロテープ) peeling test was performed on the inner bending part. After the peeling test, the peeling area of ​​the coating on the inner bending surface was measured. The area within 3 mm from the vertex of the bending part on the inner bending surface, that is, the area of ​​30 mm × 6 mm, was taken as the inner bending part, and the processability was evaluated by the ratio of the area of ​​the plating peeling to the area of ​​the inner bending part. Regarding the evaluation of processability, the following "B" was set as unqualified, and "A" to "S" were set as qualified.

[0246] When the peeling area exceeds 10%: "B"

[0247] When the peeling area is more than 5% and less than 10%: "A"

[0248] When the peeling area is 5% or less: "AA"

[0249] No peeling case: "S"

[0250] As shown in Table 1A to Table 5B, No. 4 to 25, 27, 28, 30, 32, 33, 35 to 37, 39, 40, 43 to 45, 47, 48, 53 to 58 (all examples) are manufactured by the preferred cooling conditions of the present invention, and the average chemical composition of the coating is within the appropriate range, and the area ratio of the phase and structure of the coating is within the appropriate range. As a result, the chemical corrosion resistance, water corrosion resistance, running water corrosion resistance and processability become excellent. It should be noted that the Zn content in the coating of the examples is 50% or more.

[0251] No. 1 to 3 (comparative examples) have low Al and Mg contents, and the area ratio of the MgZn2 phase and the [ternary eutectic structure of Al / MgZn2 / Zn] is out of the appropriate range. In addition, the manufacturing conditions are out of the preferred range. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0252] No. 26 (comparative example) has a small amount of Mg, and the area ratio of the MgZn2 phase is out of the appropriate range. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0253] No. 29 (Comparative Example) has an excessive amount of Sn, and thus, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0254] No. 31 (Comparative Example) has an excessive amount of Bi, and thus, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0255] No. 34 (comparative example) has an excessive amount of In. In addition, the manufacturing conditions are out of the preferred range. Furthermore, ([Al] + [Zn-Al]) / [Al-Zn] becomes less than 0.8. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance and processability become inferior.

[0256] The amount of La and Ce in No. 38 (comparative example) is excessive. In addition, the manufacturing conditions are out of the preferred range. Furthermore, ([Al] + [Zn-Al]) / [Al-Zn) becomes less than 0.8. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance and processability become inferior.

[0257] No. 41 (Comparative Example) has an excessive amount of Sr. In addition, the manufacturing conditions are out of the preferred range. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0258] The amount of Mg in No. 42 (comparative example) was excessive. Furthermore, the area ratio of the MgZn2 phase was out of the appropriate range. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability were inferior.

[0259] No. 46 (Comparative Example) has an excessive amount of P. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0260] The amount of Al and Ca in No. 49 (comparative example) is excessive. In addition, the manufacturing conditions are out of the preferred range. Furthermore, ([Al] + [Zn-Al]) / [Al-Zn] becomes less than 0.8. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance and processability become inferior.

[0261] No. 50 (comparative example) has excessive Al and Mg contents. In addition, the manufacturing conditions are out of the preferred range. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability are inferior.

[0262] No. 51 (Comparative Example) has an excessive amount of Al, and thus, its chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and workability are inferior.

[0263] The amount of Al in No. 52 (comparative example) was excessive. In addition, the manufacturing conditions were out of the preferred range. Furthermore, the total amount of Al phase, Al-Zn phase, and Zn-Al phase exceeded 75%. As a result, the chemical corrosion resistance, wet corrosion resistance, running water corrosion resistance, and processability became inferior.

[0264] [Table 1A]

[0265]

[0266] [Table 1B]

[0267]

[0268] [Table 1C]

[0269]

[0270] [Table 2A]

[0271]

[0272] [Table 2B]

[0273]

[0274] [Table 2C]

[0275]

[0276] [Table 3A]

[0277]

[0278] [Table 3B]

[0279]

[0280] [Table 3C]

[0281]

[0282] [Table 4A]

[0283]

[0284] The underlined part indicates that it is outside the scope of the present invention.

[0285] [Table 4B]

[0286]

[0287] The underlined part indicates that it is outside the scope of the present invention.

[0288] [Table 5A]

[0289]

[0290] [Table 5B]

[0291]

Claims

1. A plated steel material comprising a steel material and a plating layer disposed on a surface of the steel material, wherein the average chemical composition of the plating layer comprises, in mass %,: Al:10.0%~40.0%、 Mg: more than 4.0% and less than 8.5%, Si: 0% to 5.0%, Ca: 0% to 3.00%, Sn: 0% to 3.00%, Bi: 0% to 1.00%, In: 0%~1.00%, Y:0%~0.50%、 La: 0% to 0.50%, Ce: 0% to 0.50%, Sr:0%~0.50%、 B:0%~1.00%、 P:0%~0.50%、 Cr:0%~0.25%、 Ti: 0% to 0.25%, V:0%~0.25%、 Zr:0%~0.25%、 Ni: 0% to 1.00%, Co: 0% to 0.25%, Nb: 0% to 0.25%, Cu: 0% to 1.00%, Mn: 0% to 0.25%, Mo: 0% to 0.25%, W:0%~0.25%、 Ag: 0%~1.00%, Li: 0% to 0.50%, Na: 0% to 0.05%, K:0%~0.05%、 Fe: 0% to 5.00%, Sb: 0% to 0.50%, Pb: 0% to 0.50%, Ba: 0% to 0.25%, The rest: Zn and impurities, In the cross section of the coating layer perpendicular to the surface of the steel material, the structure observed by a scanning electron microscope is as follows in terms of area fraction: MgZn2 phase: 10% to 50%, Total of Al phase, Al-Zn phase and Zn-Al phase: 15% to 75%, [Al / MgZn2 / Zn ternary eutectic structure]: 0% to 65%, The remaining part: 0% to 5.0%, An area ratio of the total of the Al phase and the Zn—Al phase to the Al—Zn phase (([Al]+[Zn—Al]) / [Al—Zn]) is 0.8 or more.

2. The plated steel material according to claim 1, wherein: In the average chemical composition of the coating, Si is 0.05% to 5.0%. In the surface layer from the surface of the plated layer to a depth of 0.5 μm, the intensity integration value of each element when depth analysis is performed by the GDS method satisfies the following formula (1): IΣ(Si) / (IΣ(Zn)+IΣ(Al))≥0.005 (1) Here, IΣ(Si), IΣ(Zn), and IΣ(Al) in formula (1) are the intensity accumulation values ​​of Si, Zn, and Al detected by the GDS method, respectively.

3. The plated steel material according to claim 1 or claim 2, wherein: In the average chemical composition of the coating, Ca is 0.01% to 3%. The coating contains Ca3Al2Si2 phase, CaAl2Si2 phase, CaAl2Si2 phase, CaAl 1-x Si 1+x Any of the phases, where x = 0 to 0.2, In the surface layer from the surface of the plating layer to a depth of 0.5 μm, the intensity integration value of each element when the depth analysis is performed by the GDS method satisfies the following formula (2): IΣ(Ca) / IΣ(Si)≥2.0 (2) Here, IΣ(Ca) and IΣ(Si) in the formula (2) are the intensity integration values ​​of Ca and Si detected by the GDS method, respectively.

Citation Information

Patent Citations

  • Hot-dip zn-al base alloy plated steel sheet improved in heat resistance and its production

    JP2000265255A

  • Metal-coated steel strip

    JP2012528244A

  • MOLTEN Al-Zn-Mg-Si PLATED SHEET STEEL AND PRODUCTION METHOD THEREOF

    JP2016166414A

  • HOT DIP Zn-Al-Mg BASED PLATED STEEL MATERIAL

    JP2021195564A

  • Existing pile removing device

    JP2022136497A